KETERASINGAN DALAM NOVEL HARD TIMES KARYA CHARLES DICKENS - PUADINO, MOH. ABDI GUNAWAN RAHMAD (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research entitled â€œAlienation as reflected on Charles Dickensâ€™s Hard Timesâ€ is written to find out the phenomena of alienation. Alienation is a big issue in society and personality. The problem to be researched is how the characteristic of Alienation revealed in the novel Hard times. The objective of this research is to identify, classify and analyze the phenomena of alienation revealed through the perspective of character. This is a qualitative research with descriptive method. To identify and classify the types of Alienation on this novel, researcher uses the theory from Karl Marx, where he categorizes alienation into four types; they are alienation from product, from work, from their self and from another man. Then Robertâ€™s character analysis is used to reflect each phenomena of Alienation found of this novel base on the perspective of character and authorâ€™s narration.The result of this research reveals that the type of alienation which commonly appears in novel is the alienation from work. Two of the main character Louisa and Thomas Gradgrind Jr. experience alienation because they was forced by people around them to do something that they do not want. Most of the Alienation found trough the statement from other character.Â Â  They define, force and dictate others to do or behave base on their will. Like shown by Josiah Bounderby and Thomas Gradgrind toward their family and friends. Key Words: Alienation, Novel and Character.